Assessing the Quality of Urban Life in New Algerian Cities: The Case of Sidi Abdellah - Gueham Youcef; Omar Tamelghaghet (International Journal of Computational and Experimental Science and Engineering, 2025)
This study assesses the level of urban quality of life in the new city of Sidi Abdellah, Algeria. It addresses the central research question: do modern urban communities represented by new cities meet the standards of quality urban life for their residents? The research investigates whether these emerging urban centres act as attractive hubs that fulfil residents' needs and foster both residential and spatial satisfaction. The theoretical framework identifies the essential human and environmental needs that enhance the overall quality of life. On the applied side, the study employs multiple contemporary urban design indicators and evaluation methods to measure and analyse urban quality of life. The objective is to establish a localised Algerian reference framework or code for assessing urban quality of life. The findings reveal that improving quality of life in new cities requires active community participation within sustainable regulatory frameworks and the adoption of a unified measurement approach capable of evaluating quality-of-life standards in high-density urban environments.